If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying e + -885 = -21e + -5 Reorder the terms: -885 + e = -21e + -5 Reorder the terms: -885 + e = -5 + -21e Solving -885 + e = -5 + -21e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '21e' to each side of the equation. -885 + e + 21e = -5 + -21e + 21e Combine like terms: e + 21e = 22e -885 + 22e = -5 + -21e + 21e Combine like terms: -21e + 21e = 0 -885 + 22e = -5 + 0 -885 + 22e = -5 Add '885' to each side of the equation. -885 + 885 + 22e = -5 + 885 Combine like terms: -885 + 885 = 0 0 + 22e = -5 + 885 22e = -5 + 885 Combine like terms: -5 + 885 = 880 22e = 880 Divide each side by '22'. e = 40 Simplifying e = 40
| 14x-9=-80x-8x | | -8h+-26=37+13h | | -7b+39=b+223 | | (7b-10)=180 | | x^2=x*5 | | 23y+82= | | 7z-4=12 | | 14s+5=s-528 | | -4(2x-5)+13x=15 | | x+299=-6x-9 | | -3x-6=x+122 | | 17x+146=27 | | p-186=-3p-6 | | x-86=-6x-9 | | x^2+22x+4=0 | | 9600=16000+-1600y | | (5x^2+7x+4)-(5x^2+5)=9x+16 | | -5x+4=x+142 | | 6x^3+17x^2-63x+10=-5 | | a^2-16a-36=0 | | x-(2x+1)=-(3x+3)+2 | | 50-(5x+13)=5(x+3)+x | | 3z+12=67+10 | | (x^4)+(6x^3)-(24x)+26= | | (5x^2+7x+4)-(5x^2+5)=9x+5 | | x+269=-9x+9 | | 56t=62.7t-75.24 | | 14+6t=1t | | 22x-7-12x+4=20x-9-10x+16 | | x-79=-x-3 | | -x-4=x+66 | | b+183=-8b-6 |